2020
DOI: 10.1101/2020.02.04.932236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tourism-driven ocean science for sustainable use: A case study of sharks in Fiji

Abstract: The oceans are in a state of rapid change -both negatively, due climate destabilization and misuse, and positively, due to strengthening of policies for sustainable use combined with momentum to grow the blue economy. Globally, more than 121 million people enjoy nature-based marine tourism -e.g., recreational fishing, diving, whale watching -making it one of the largest marine sectors. This industry is increasingly threatened by ocean degradation and management has not kept pace to ensure long-term sustainabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 64 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…This hypothesis could be tested by monitoring other dive sites, feeding and not, in Fiji where bull sharks are encountered. Ward-Paige et al (2020) reported bull shark groups of variable sizes from six areas in Fiji. Individuals would need to be independently identified at these sites to ensure that they are also visitors to the SRMR and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis could be tested by monitoring other dive sites, feeding and not, in Fiji where bull sharks are encountered. Ward-Paige et al (2020) reported bull shark groups of variable sizes from six areas in Fiji. Individuals would need to be independently identified at these sites to ensure that they are also visitors to the SRMR and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, declines and regional extinctions of marine species often go undocumented, but can be inferred from local knowledge (Dulvy & Polunin, 2004; Jabado et al, 2015; Abudaya et al, 2018; Mason et al, 2020). Additionally, fishers are key stakeholders and can provide socio‐ecological perception and knowledge on natural resource conservation needs (McNeill, Clifton & Harvey, 2018), existing legislation and trade, which are all essential for developing effective conservation strategies (Jabado et al, 2015; Liao, Huang & Lu, 2019; Patankar, 2019; Mason et al, 2020; Ward‐Paige, Brunnschweiler & Sykes, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Wildlife provisioning also creates unprecedented opportunities for scientific data collection, aggregating animals that are difficult to study without baiting due to their low density, solitary behavior, or pelagic environment (Bègue et al, 2020 ; Brena et al, 2015 , 2018 ; Gallagher & Hammerschlag, 2011 ; Meyer et al, 2009 ). Flourishing shark and ray watching also promotes the development of participatory science, involving tourists in the production of scientific research and raising their awareness on elasmobranch conservation (Gallagher et al, 2015 ; Mieras et al, 2017 ; Ward‐Paige et al, 2020 ). Finally, the ecological and economic importance of elasmobranchs for local communities has the potential to enhance the creation of protected areas to better conserve these often highly threatened species and potentially benefit the entire ecosystem (Govan et al, 2008 ; Jupiter et al, 2014 ; Ward‐Paige et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Flourishing shark and ray watching also promotes the development of participatory science, involving tourists in the production of scientific research and raising their awareness on elasmobranch conservation (Gallagher et al, 2015 ; Mieras et al, 2017 ; Ward‐Paige et al, 2020 ). Finally, the ecological and economic importance of elasmobranchs for local communities has the potential to enhance the creation of protected areas to better conserve these often highly threatened species and potentially benefit the entire ecosystem (Govan et al, 2008 ; Jupiter et al, 2014 ; Ward‐Paige et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation